PALEOGENE HARES (LEPORIDAE, LAGOMORPHA) FROM THE ZAISAN DEPRESSION (EASTERN KAZAKHSTAN) - Erbajeva M.A. (My University, 1999)
The Oligocene Leporidae from the Zaisan Depression (Eastern Kazakhstan) collected by the Joint Kazakhstan-American Paleontological Expedition during 1993 and 1994 are described. A new genus and species of the family Leporidae, Zaissanolagus gromovi gen. et sp. nov., is described. This form was previously referred to as Procaprolagus cf. vetustus (Burke, 1941). The species Zaissanolagus danjiangensis (Tonget Lei, 1987) originally described as a member of the genus Lushilagus Li, 1965 should be assigned to this genus. The teeth belonging to the genus Gobiolagus are described briefly.
Keywords: Paleogene; Cenozoic::Paleogene; Кайнозой::Палеоген